EXPERIMENTAL DETERMINATION OF THE REACTION DOLOMITE + 2 COESITE = DIOPSIDE + 2 CO2 TO 6 GPA - Luth R.W. (My University, 1996)
The carbonation reaction CaMg(CO3)2 (dolomite)+2SiO2 (coesite)=CaMgSi2O6 (diopside)+2 CO2 (vapor) has been determined experimentally between 3.5 and 6 GPa in a multiple-anvil, solid-media apparatus. This reaction, a candidate for carbonation of eclogites (garnet+clinopyroxene) in the Earth’s mantle, lies at higher pressure for a given temperature than do the carbonation reactions for peridotites (olivine+orthopyroxene±clinopyroxene). A depth interval may exist within the Earth’s mantle under either ‘normal’ or ‘subduction’ thermal regimes where carbonated peridotite could coexist with carbonate-free, CO2-bearing eclogite.